The context does matter: Relationship between abandoning university degree and contextual variables (European Journal of Education and Psychology, 2018)
University dropout is a global problem that affects almost every university in the world and whose consequences affect not only to the development of the deserter, but also to the society in which one this lives. The European University Dropout Integrated Management Project (GUIDE), coordinated by the Polytechnic University of Madrid and implemented by 21 higher education institutions, assumes this approach and adopts among its lines of action, to develop the scientific knowledge of the problem. Thus the participating institutions have developed a parallel research, whose joint results are still being analyzed. The University of Oviedo, partner institution of the GUIDE project reported here the results obtained in this study. Descriptive, correlational and multivariate analysis of variance (MANOVA) have been conducted on a sample of 1,311 subjects, identifying the variables that maintain relations with the phenomenon in different contexts. Between the results, the role of the variables related to the student are highlighted.